A influência da cultura organizacional, suporte e coping no bem-estar dos trabalhadores: uma comparação entre os métodos de Baron & Kenny e Hays e Preacher - Sohler, Flavio Augusto Settimi (2013)
The main objective of this study is to assess the effect of the organizational culture (which is measured by the organizational values and practices) upon the positive and negative past experiences related to the job well being, being such relationship mediated by the organizational support and coping. Therefore, there were adopted the scales of positive and negative past experiences related to the job well being; the Brazilian tool for the Organizational Culture assessment; Perceived Organizational Support and Coping Scales. The employees of a federal government company took part in this research. This assessment adopted some methodological procedures for analysis classified as qualitative and quantitative. The data analysis demonstrated that the two factors, the cooperative professionalism values and the employees satisfaction and well being, were predictors of the positive affection. Moreover, it identified that cooperative professionalism values and the practices for promoting the interpersonal relationship are negatively associated with the negative affections. Such results have demonstrated that, more the company comes out with a cooperative culture value, bigger are the positive experience with its work force, on the other hand, smaller are the negative ones. The cooperative professionalism value, the employees satisfaction and well being were both predictors of the control coping. In its turn, the control coping was the predictor of either the positive and negative affections. However, the coping was not a mediator between the organizational culture and the job well being. As results have shown, once the employee perceptions regarding the organizational support and values and organizational practices were well consolidated among the employees, they could be appointed as relevant dimensions for the positive organization towards promoting the workers well being.